Moulage: The exercise of criation (ModaPalavra e-periódico, 2015)
This article presents a study on the use of moulage technique as a way to create and develop innovative products for the fashion design. The goal is to address the importance of this tool in the creative process and the generation of new concepts and forms from this method. The efficacy of the same in driving the dynamic process of transforming ideas and materials fashion products makes feasible the creation, insofar as it gives wayto induce new perspectives translated into innovative constructive forms and configuring a new silhouette. The results were obtained through the empirical study with literature review and testing exercise. Thus, it was understood that the handling of the fabric directly on the dummy enables rapid visualization of shape, volume and silhouette. Was the proposal to provide an additive technique during the process, or assist designers whose ability to design is limited.
Keywords: moulage; innovation; design; creation